Tasks as a link between technology introduction and continuing training : evidence of a mediating mechanism in firms - Baum, Myriam [Verfasser] (My University, 2026)
"New technology is changing the skills that employers demand and the tasks that employees perform. Technological change is therefore increasing the need for continuing vocational training. However, little is known about the association between technology introduction, employees' job tasks and continuing training participation in firms. Employees' job tasks may mediate the relationship between technology introduction and continuing training participation. As tasks are distributed unequally among employees, tasks may reinforce inequality in continuing training. This study uses German firm‐level data (BIBB Training Panel, n = 1057) to identify such a mediating effect. The results show that the association of technology, tasks and continuing training varies depending on the form of continuing training. Technology introduction does directly affect informal continuing training rates, but not course‐based continuing training rates. Nevertheless, technology introduction does increase the frequency of all types of tasks in firms. Moreover, manual tasks have a direct negative effect on the course‐based continuing training rates. The results suggest that manual tasks mediate the relationship between technology introduction and course‐based continuing training. Also, the results highlight the importance of tasks for reinforcing inequalities in continuing training participation in times of technological change." (Author's abstract ; BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; G 2.2.1 Technologisierung; G 2.3 Wandel von Arbeit & Wirtschaft; 370; 330; Berufliche Weiterbildung; Weiterbildungsbeteiligung; Weiterbildungsmaßnahme; Technischer Wandel; Tätigkeitsmerkmal; Tätigkeitswandel; BIBB-Qualifizierungspanel